2018
DOI: 10.1093/cid/cix1116
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Cannabis Use Associated With Reduction in Activated and Inflammatory Immune Cell Frequencies in Antiretroviral Therapy–Treated Human Immunodeficiency Virus–Infected Individuals

Abstract: While the clinical implications are unclear, our findings suggest that cannabis use is associated with a potentially beneficial reduction in systemic inflammation and immune activation in the context of antiretroviral-treated HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 44 publications
6
73
0
Order By: Relevance
“…Our results are consistent with a previous study reporting that cannabis use was associated with lower plasma HIV RNA levels among recently infected PLWH [7], and with reports of reduced HIV replication and cellular infection rates in the presence of cannabinoids in vitro [19,20]. Further, cannabis use has been associated with decreased frequencies of interleukin 23 and tumor necrosis factor α [8] and, more recently, with the reduction of interferon-γ inducible protein 10 levels in plasma [21]. Altogether, these findings point to a potential anti-inflammatory effect of cannabis that, in turn, might positively impact HIV replication and persistence [22], although another study has suggested that tetrahydrocannabinol may enhance HIV replication by suppressing immune functions in mice [23], and this possibility should be evaluated in future, larger clinical studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with a previous study reporting that cannabis use was associated with lower plasma HIV RNA levels among recently infected PLWH [7], and with reports of reduced HIV replication and cellular infection rates in the presence of cannabinoids in vitro [19,20]. Further, cannabis use has been associated with decreased frequencies of interleukin 23 and tumor necrosis factor α [8] and, more recently, with the reduction of interferon-γ inducible protein 10 levels in plasma [21]. Altogether, these findings point to a potential anti-inflammatory effect of cannabis that, in turn, might positively impact HIV replication and persistence [22], although another study has suggested that tetrahydrocannabinol may enhance HIV replication by suppressing immune functions in mice [23], and this possibility should be evaluated in future, larger clinical studies.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, 1 study has demonstrated beneficial impacts of cannabis on plasma HIV RNA among recently infected people living with HIV (PLWH) [7]. More recently, Manuzak et al [8] evaluated the impact of cannabis use on inflammation and immune activation in ART-treated PLWH and reported that cannabis use was associated with (1) reduced activation of CD4 + and CD8 + T cells and (2) a shift in the composition of the monocyte populations in peripheral blood.…”
mentioning
confidence: 99%
“…28 Heavy cannabis use has also recently been shown to be associated with reduction of activated and inflammatory immune cells among HIV-positive patients on antiretroviral treatment. 29 While there is some macaque evidence of how a cannabis-induced lower inflammatory response could influence HIV viral load, 30 such results need to be combined with behaviors to establish the clinical relevance of this effect to transmission and acquisition of HIV and other STIs. While our findings did not show in a difference by cannabis use in viral load among our participants with HIV, reduced inflammation rectally could reduce probability of acquisition of rectal STIs.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, cannabinoid use prevented induction of pro-inflammatory CD16 + monocytes and production of IP-10, suggesting anti-inflammatory effects in humans [48]. In another human study, in addition to reduction of pro-inflammatory monocytes, heavy cannabis use was also associated with decreased frequencies of HLA-DR + CD38 + activated CD4 and CD8 T-cells and frequencies of IL-10, IL-12 and TNFα -producing antigen presenting cells compared to non-cannabis users [49]. The anti-inflammatory effects of cannabinoids are now under investigation in clinical trials, as such, our team in now conducting a clinical trial in the context of HIV infection [50].…”
Section: Cannabidiol To Decrease Sars-cov-2 Associated Inflammationmentioning
confidence: 93%